Method for measuring the bonding strength between metal substrate and oxide film using SEM in-situ tensile tester

The SEM in-situ stretcher measures the bonding force at the interface between the metal matrix and the oxide film, which solves the problem that the existing technology cannot quantitatively measure the bonding strength, and realizes accurate prediction of the oxidation peeling of high-temperature components, and improves supercritical CO2 braking Safety of Duncyclic power generation technology.

CN115078086BActive Publication Date: 2025-01-14NORTH CHINA ELECTRIC POWER UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202210538093.8
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-05-18
Publication Date
2025-01-14
Estimated Expiration
2042-05-18

AI Technical Summary

Technical Problem

The existing measurement methods cannot accurately measure the bonding strength between the metal matrix and the oxide film interface, especially in high-temperature and high-pressure supercritical CO2 environment, which leads to the inability to effectively predict the peeling of the oxide scale of high-temperature components, affecting the supercritical CO2 Breton cycle. Development of power generation technology.

Method used

The method of measuring the bonding force of the metal matrix and oxide film by using SEM in situ stretching meter, by preparing in situ tensile samples of specific sizes and shapes, combined with real-time observation of scanning electron microscope and tensile rate control of in situ tensile meter , record the displacement-tension force curve, calculate the tensile strength of the oxide film and the interface shear force, and realize quantitative measurement of the bonding strength of the brittle oxide film and plastic metal matrix.

Benefits of technology

It improves the accuracy and real-time measurement, can clearly observe the crack initiation to fracture process, provides an interface splitting mechanism, and provides a quantitative reference for the corrosion and failure of materials in supercritical carbon dioxide environment, avoiding the limitations of qualitative measurement of traditional methods.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115078086B_ABST
    Figure CN115078086B_ABST
Patent Text Reader

Abstract

A method for measuring the interface bonding force between a metal matrix and an oxide film based on an SEM in-situ tensile instrument, the purpose of which is to provide an in-situ tensile method for quantitatively measuring the bonding force between a metal matrix and an oxide film, which can reveal the cracking process and mechanism analysis of a plastic metal matrix and a brittle oxide film system. The method of the invention is as follows: first, sample preparation and pretreatment; second, in-situ tensile test of the sample, recording the displacement-tension curve and corresponding data; third, measuring the stress-strain curve of the oxide film-free matrix material in the same temperature environment and recording the data; fourth, calculating the tensile strength σ of the oxide film when the crack density is steady-state f ; Fifth, the parameters are substituted into the formula #imgabs0##imgabs1# to calculate the bonding force between the metal substrate and the oxide film. The present invention can quantitatively measure the bonding force between the metal substrate and the oxide film, and the method is simple to operate, easy to implement and highly accurate.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for measuring bonding strength based on SEM in-situ stretching, and in particular to a method for measuring the bonding strength of an interface between a metal substrate and an oxide film by using a SEM in-situ stretching instrument. Background Art

[0002] Improve energy conversion efficiency and reduce CO 2 Emissions have always been the goal pursued by the energy and power industry. Increasing the temperature and pressure of the main steam can effectively improve the energy conversion efficiency. However, the high-temperature service performance of metal materials limits the development of advanced energy conversion systems, among which the high-temperature key components of boilers are in high-temperature and high-pressure supercritical CO 2 The oxidation and carbonization corrosion of the environment are particularly critical. The over-temperature and tube burst caused by the rapid oxidation and peeling of the high-temperature heating surface pipes of the boiler directly affect the supercritical CO 2 The development of new Brayton cycle power generation technology. Therefore, the measurement of the bonding strength between the oxide film and the substrate under the unit service environment can help predict the peeling of the oxide scale of high-temperature components, which can effectively reduce the over-temperature and pipe burst accidents caused by peeling.

[0003] Most existing measurement methods are qualitative measurements, which define the strength of oxide film bonding by passing or failing, such as bending method, indentation method and scratch test. These methods cannot give quantitative values ​​and have limited guiding significance for on-site engineering. Liu et al. (HY Liu, Y G Wei, L H Liang, X H Liu, Y B Wang, HS Ma. Damage characterization model of ceramic coating systems based on energy analysis and bending tests [J]. Ceramics International, 2018, 44 (5): 4807-4813.) disclosed a quantitative damage model of ceramic coating systems based on the three-point bending method. The limitation of this method is that it is only applicable to weak interface systems. When the film-substrate interface bonding strength is higher than the bonding strength of the adhesive, this method cannot effectively measure the interface bonding performance. Song et al. (SONG YN, XU BS, WANG HD, et al. Failure Process Analysis of PlasmaSprayed Coatings under Tip Load Based on Acoustic Emission Signals [J]. Surface Engineering, 2014, 30 (9): 675-682.) conducted surface indentation tests on three coatings with different bonding strengths, namely Al2O3, Al2O3-TiO2 and FeCrBSi, and analyzed and extracted the distribution characteristics of the amplitude and energy of the acoustic emission signal during the test. They combined the indentation method with the acoustic emission technology to measure the interface bonding strength. The simple indentation method for measuring bonding strength cannot accurately obtain the critical load when the film peels off due to the fixed indentation load, and the quality standard classification is vague, so it is only used as a qualitative characterization of the film bonding strength.Lu et al. (Ping Lu, Humberto Gomez, Xingcheng Xiao, Michael Lukitsch, Delcie Durham, Anil Sachdeve, Ashok Kumar, Kevin Chou, Coating thickness and interlayer effects on CVD-diamond film adhesion to cobalt-cemented tungsten carbides [J]. Surface and Coatings Technology, 2013, 215: 272-279.) studied CVD diamond film on cemented carbide surface and found that the interface bonding strength obtained by scratch method was approximately linearly positively correlated with the film thickness, that is, it increased with the increase of film thickness. It can be seen that the physical meaning of the critical load measured by scratch method is not clear. Some scholars even believe that the critical load Lc of scratch method has no definite relationship with the interface bonding performance, but is only a reflection of the bearing capacity of the film-based system.

[0004] The present invention is based on the matrix stretching method of the SEM in-situ stretching instrument, which can not only adjust the moving rate of the stretching table and simulate the actual operating temperature of the sample, but also reflect the condition of the oxide film on the surface of the sample in real time, which is beneficial to the control of the growth and diffusion of the oxide film cracks at the target position under actual working conditions. Therefore, the accuracy of the overall measurement is improved, and the final measurement result is more in line with the actual situation. Summary of the invention

[0005] The present invention provides a method for measuring the interfacial bonding force between a metal substrate and an oxide film by using a SEM in-situ tensile tester. The method can control the stretching rate and observe the cracking of the surface oxide layer in real time. The measurement result is in line with reality and has good accuracy.

[0006] A test method for measuring the interfacial bonding strength between a metal substrate and an oxide film using an SEM in-situ tensile tester, the specific implementation steps are as follows:

[0007] Step 1: Prepare the metal specimen for in-situ tension:

[0008] Select a long strip of plastic metal as the specimen, the specific shape is wide on both sides and narrow in the middle, and pre-make U-shaped notches on both sides of the center of the specimen;

[0009] Step 2: Pretreatment of the sample:

[0010] The sample is ground and polished to further flatten the surface; the flat sample is cleaned and dried before being subjected to corrosion tests to form an oxide film;

[0011] Step 3: Perform in-situ tensile test:

[0012] Fix the sample on the fixture of the in-situ stretching table. After the fixation is completed, install the in-situ stretching table in the SEM sample chamber. When the sample on the in-situ stretching table is installed in the SEM sample chamber, the full view of the U-shaped notch must be visible through the scanning electron microscope;

[0013] Step 4: Enter the parameters for data processing: First calculate the tensile strength σ of the oxide film when the crack density reaches a steady state f , where its calculation expression is Where S 1 is the cross-sectional area of ​​the oxide film with a thickness of δ, S 2 is the cross-sectional area of ​​the substrate that has not been oxidized, S 3 is the cross-sectional area of ​​the substrate material without oxide film.

[0014] The present invention also discloses a method for applying the above-mentioned test method for measuring the interface bonding force between a metal matrix and an oxide film by using a SEM in-situ tensile tester to the design of a boiler high-temperature heating surface pipeline.

[0015] Beneficial effects:

[0016] The invention is based on a SEM in-situ tensile instrument, utilizes an in-situ tensile specimen with a special size and shape to perform a matrix tensile method, and tests the bonding strength between a brittle oxide film and a plastic metal matrix.

[0017] With the help of the real-time image of the scanning electron microscope and the specific stretching rate of the in-situ tensile instrument, the process from crack initiation to complete fracture of the brittle oxide film and the plastic metal matrix system can be clearly observed. Through the scanning electron microscope observation, the real-time video recording function of the scanning electron microscope is used to record the whole process of crack initiation, expansion, and contraction on the surface of the brittle oxide film of the oxidized sample during the stretching process until the system is completely fractured. At the same time, the stretching rate of the in-situ stretching table is controlled in real time by computer software to obtain the displacement-tension curve of the sample during the stretching process for subsequent analysis of its mechanical properties. The microscopic morphology observed by the scanning electron microscope during the in-situ tensile experiment and the displacement-tension curve characterization results recorded by the software are combined to reveal the splitting mechanism between the brittle oxide film and the plastic metal matrix, providing a reference for the corrosion and failure of the material in the supercritical carbon dioxide environment. This method is suitable for the measurement of the interface bonding strength of all brittle oxide films and plastic metal matrix systems. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a schematic diagram of the process of the present invention.

[0019] Figure 2 This is a schematic diagram of the SEM in-situ tensile specimen described in step 1 of the present invention.

[0020] Figure 3The displacement-tension curve obtained by in-situ tensile test on the sample.

[0021] Figure 4 This is the microscopic morphology of the oxide film with an in-situ stretching ratio of 0.769%.

[0022] Figure 5 This is the microscopic morphology of the oxide film with an in-situ stretching ratio of 2.516%.

[0023] Figure 6 This is the microscopic morphology of the oxide film with an in-situ elongation of 3.422%. DETAILED DESCRIPTION

[0024] A method for measuring the interfacial bonding strength between a metal substrate and an oxide film using an SEM in-situ tensile tester, characterized by comprising the following steps:

[0025] Step 1: Prepare a metal specimen for in-situ stretching;

[0026] Select a long strip of plastic metal as the specimen, the specific shape is wide on both sides and narrow in the middle, and pre-make U-shaped notches on both sides of the center of the specimen;

[0027] The total length L of the metal substrate 1 =45mm, width W 1 =8.5mm, thickness H=0.8mm, four arc chamfer radius R=10±0.1mm;

[0028] The test area of ​​the metal is a U-shaped notch, the length of which is L 2 =8mm, width W 2 =2.5mm, thickness H=0.8mm, the depth of the prefabricated U-shaped notch is the transition fillet radius, and the transition fillet radius R=30±0.1mm.

[0029] The size and shape of the specimen are as follows: Figure 2 As shown. The prefabricated U-shaped notch is to meet the requirements of the SEM observation field of view. The selection of other styles of notches exceeds the SEM observation range. If cracks appear in the range beyond the field of view during the stretching process, they cannot be observed, which will cause errors in the stress-strain data recording of the initial crack. The size of the prefabricated metal matrix and the U-shaped notch is a comprehensive consideration of the size of the in-situ stretching table. If the length and thickness are too small, the clamp of the stretching table cannot firmly fix the sample, which will cause the sample to fall off the stretching table during the stretching process, causing the experiment to fail; if the length and thickness are too large, it exceeds the maximum size that the stretching table can fix and exceeds the travel of the stretching table, and the experiment cannot be carried out. The data selected in this experiment is a moderate size selected based on the SEM field of view, the size of the stretching table clamp, and the travel of the stretching table. It can not only ensure the smooth progress of the experiment, but also achieve the optimal observation field of view, the maximum travel distance, and the most stable fixation.

[0030] Step 2: Pretreatment of the sample:

[0031] (1) Grind both sides of the specimen using 500#, 800#, 1000#, and 1500# sandpaper, and then polish using diamond paste with a particle size of 1 μm to further smooth the surface;

[0032] (2) Place the sample after the operation in a beaker containing anhydrous ethanol. The anhydrous ethanol must completely cover the sample. Place the beaker in an ultrasonic cleaner and clean it for 5 minutes, then take it out and dry it.

[0033] (3) The cleaned samples were placed in a sealed high-pressure reactor at 650°C and 25 MPa supercritical carbon dioxide environment for 800 hours of corrosion testing to form an oxide film.

[0034] The reason for selecting the sandpaper type in (1) is that the surface of the processed sample is relatively rough. In order for the subsequent oxide film to adhere intactly and observe the deformation morphology, sandpaper is needed for grinding. The initial sandpaper is selected as 500# because the initial surface roughness of the sample is not very large. If sandpaper less than 500# is used at the beginning, deep scratches will be produced on the surface of the sample, which is not conducive to subsequent observation. The gradient grinding method is adopted to gradually smooth the surface of the sample. If the difference in sandpaper parameters is too large, the scratches on the surface will be difficult to smooth, which is not conducive to the adhesion and observation of the oxide film.

[0035] Using anhydrous ethanol for cleaning for 5 minutes can remove impurities on the surface caused by grinding. Compared with clean water, anhydrous ethanol contains fewer impurities and will not cause secondary residues of impurities. Cleaning for 5 minutes is a reasonable time. Increasing the time will not significantly help clean impurities and the efficiency is low.

[0036] The service environment of supercritical carbon dioxide units is mostly 650℃, 25Mpa. The corrosion in this environment can restore the real service environment to the greatest extent, making the results more convincing. Considering the size of the sample, 800 hours is enough to generate a clear oxide film. The growth rate of the carbide layer is extremely slow. Continuing to increase the time can increase the thickness of the carbide layer, but the increase is very small and has little impact on the experimental results.

[0037] Step 3: Perform in-situ tensile test:

[0038] Fix the prepared sample on the fixture of the in-situ stretching table. After the fixation is completed, install the in-situ stretching table in the SEM sample chamber. When the sample on the in-situ stretching table is installed in the SEM sample chamber, the full view of the U-shaped notch must be visible through the scanning electron microscope;

[0039] The sample chamber is sealed and evacuated. After ensuring that the sample chamber is vacuumed, the sample is heated by electric heating. After reaching the target temperature of 650°C, the stretching speed of the in-situ stretching table is set to 1μm / s and the stretching is started. The stretching rate of 1μm / s ensures that the observer can clearly capture the process of crack growth, ensuring efficiency and effect.

[0040] During the in-situ stretching process, the growth and expansion process of the oxide film cracks were observed. The cracks first initiated at the upper and lower boundaries of the oxide film. Because the oxide film growing at the boundary has a large number of voids due to positional limitations, the crack growth resistance is reduced. The cracks expand in the direction with more void defects. The displacement-tension curve was recorded in real time, and the video, pictures and displacement-tension curve of the experimental process were collected. The displacement-tension curve of this experiment is shown in the attached figure. Figure 3 As shown in the figure, the displacement-tension curve reflects the relationship between the tension applied to the sample and the deformation displacement of the sample. The stress can be obtained by dividing the tension by the cross-sectional area of ​​the U-shaped notch. The cross-sectional area is W. 2 *L 2 ; The strain can be obtained by dividing the displacement by the initial length of the U-shaped notch, and the initial length of the U-shaped notch is L 2 .

[0041] Changes in the bonding strength between the metal substrate and the oxide film, attached Figure 4 The microscopic morphology of the oxide film with an in-situ tensile rate of 0.769%. At this time, cracks just appeared on the surface of the oxide film. It can be considered that the oxide film and the substrate have begun to separate. Figure 4 The corresponding tension at this time is 446.505N, that is, the stress is 22.325Mpa, and the corresponding displacement at this time is 345μm, that is, the strain is 0.0431. The stress and strain at this time are recorded; Attached Figure 5 The microstructure of the oxide film with an in-situ elongation of 2.516%. At this time, the elongation enters the strengthening stage and uniform plastic deformation occurs. At this time, it is necessary to pay attention to whether new cracks are initiated. After this stage, the sample will soon enter the local deformation stage and the number of cracks will be stable. Figure 6 This is the microscopic morphology of the oxide film with an in-situ tensile rate of 3.422%. At this time, the stress on the oxide film reaches the top and the number of cracks is stable. The tensile force is 596.731N, that is, the stress is 29.837Mpa. The corresponding displacement is 1539μm, that is, the strain is 0.192. The stress and strain at this time are recorded.

[0042] Step 4: Bring in parameters for data processing:

[0043] Based on the collected data, enter the formula Calculate the shear force at the interface.

[0044] The formula is derived as follows: The relationship between tensile stress σ(x) and interface shear force τ(x): δ is the film thickness. For the convenience of analysis, the interface shear force τ(x) is calculated according to the sinusoidal distribution, then λ 1 is 1 The maximum crack spacing at f is the tensile strength of the layer, Where S 1 is the cross-sectional area of ​​the oxide film with a thickness of δ, S 2 is the cross-sectional area of ​​the substrate that has not been oxidized, S 3 is the cross-sectional area of ​​the substrate material without oxide film, F 2 is the strain when the crack density reaches a steady state 2 The corresponding pulling force, The strain ε of the substrate material without oxide film is measured in the same temperature environment. 2 In order to study the overall interface bonding strength and make the research phenomenon more obvious, the strain was appropriately increased to ε 2 , at this time the number of cracks reaches a stable value, so the above formula Corrected to λ 2 is the strain ε when the crack density is stable 2 The corresponding maximum crack spacing.

[0045] The present invention proposes a method for measuring the interfacial bonding force between a metal substrate and an oxide film by using a SEM in-situ tensile instrument, and introduces in detail the preparation, pretreatment and experimental process of the sample required for the method. The characterization technology operation has the characteristics of visualization of characterization, real-time observation of the process, controllable stretching rate and wide application range, and has a high experimental success rate, avoiding the problem of waste of resources due to multiple experimental failures, and has the effect of saving energy.

[0046] The present invention is prepared by preparing a total length L 1 =45mm, width W 1 =8.5mm, thickness H = 0.8mm, four arc chamfer radius R = 10 ± 0.1mm, the test area is a U-shaped notch, the length L 2 =8mm, width W 2 =2.5mm, thickness H=0.8mm, prefabricated U-shaped notch depth is transition fillet radius, transition fillet radius R=30±0.1mm metal sample, after grinding, polishing and cleaning, was corroded for 800 hours at 650℃, 25Mpa environment to obtain oxide film. The sample that has completed the preliminary work was subjected to in-situ tensile test to obtain stress-strain curve, and was substituted into the formula The bonding force between the oxide film and the substrate can be quantitatively calculated. The problem that the traditional method can only give a qualitative conclusion is solved, and the effect of numerical quantification is achieved. The above shows and describes the basic principles, main features and advantages of the present invention. Those skilled in the art should understand that the present invention is not limited to the above embodiments. The above embodiments and the specification only describe the principles of the present invention. The present invention will have various changes and improvements without departing from the spirit and scope of the present invention. These changes and improvements all fall within the scope of the present invention to be protected. The scope of protection claimed by the present invention is defined by the attached claims and their equivalents.

Claims

1. A test method for measuring the interfacial bonding strength between a metal substrate and an oxide film using an SEM in-situ tensile tester, characterized by: The steps include: Step 1: Prepare an in-situ stretched metal specimen: the total length of the metal substrate is L1=45 mm, the width is W1=8.5 mm, the thickness is H=0.8 mm, the upper and lower chamfers from the left edge to the transition zone and the upper and lower chamfers from the right edge to the transition zone, a total of four arc chamfers, the radius is R=10±0.1 mm; The experimental area of ​​the metal substrate is a U-shaped notch, where the length L2=8mm, the width W2=2.5mm, the thickness H=0.8mm, the depth of the prefabricated U-shaped notch is the transition fillet radius, and the transition fillet radius R= 30±0.1mm; A long strip of plastic metal matrix is ​​selected as the specimen, the specific shape of which is wide on both sides and narrow in the middle, and a U-shaped notch is prefabricated on both sides of the center of the specimen; Step 2: Sample pretreatment: Grind and polish the sample to further flatten the surface; clean and dry the flat sample and then conduct corrosion test to form an oxide film; use 500#, 800#, 1000# and 1500# sandpaper to grind both sides of the metal sample in sequence, and then use diamond grinding paste with a particle size of 1μm to polish and further flatten the surface; Step 3: Perform in-situ tensile test: The sample is fixed on the fixture of the in-situ stretching table. After the fixing is completed, the in-situ stretching table is installed in the SEM sample chamber. When the sample on the in-situ stretching table is installed in the SEM sample chamber, the full picture of the U-shaped notch can be seen through a scanning electron microscope; Step 4: Enter the parameters for data processing: First calculate the tensile strength σ of the oxide film when the crack density reaches a steady state f , its calculation expression is Where S1 is the cross-sectional area of ​​the oxide film with a thickness of δ, S2 is the cross-sectional area of ​​the substrate that is not oxidized, S3 is the cross-sectional area of ​​the substrate material without oxide film, and F2 is the tensile force corresponding to the strain ε2 when the crack density reaches a steady state. It is the tensile force corresponding to the strain ε2 of the substrate material without oxide film measured in the same temperature environment; Place the sample after the operation in a beaker containing anhydrous ethanol, which must completely cover the sample. Place the beaker in an ultrasonic cleaner for 5 minutes, then take it out and dry it. Place the dried sample in a sealed high-pressure reactor in a supercritical carbon dioxide environment at 650°C and 25Mpa for 800 hours of corrosion testing to form an oxide film. The step 3 further includes the following contents: sealing the sample chamber and evacuating the sample chamber, after ensuring that the sample chamber is vacuum, heating the sample by electric heating, and after reaching the target temperature, setting the stretching speed of the in-situ stretching stage to 1 μm / s, and starting in-situ stretching; During the in-situ stretching process, the growth and expansion of the oxide film cracks were observed, the displacement-tension curve was recorded in real time, the video, pictures and displacement-tension curve of the experimental process were collected, and the changes in the bonding strength between the metal substrate and the oxide film were analyzed; The step 4 further includes the following contents: Substituting the above expression into the formula Where τ is the shear stress at the interface between the metal matrix and the oxide film, which is also the bonding force between the two; δ is the thickness of the oxide film; σ f is the tensile strength of the oxide film, ε1 is the strain when the crack appears, E is the elastic modulus of the oxide film; λ1 is the maximum crack spacing when the strain is ε1; λ2 is the maximum crack spacing under strain ε2 when the crack density reaches stability.

2. The design method of boiler high temperature heating surface pipeline is characterized by: The test method for measuring the interfacial bonding strength between a metal matrix and an oxide film using an SEM in-situ tensile tester as described in claim 1 is applied to the design of high-temperature heating surface pipelines of boilers.

Citation Information

Patent Citations

  • SEM in-situ tensile test method for researching interface fracture behavior of metal matrix and ceramic film layer

    CN110967254A